VARIASI WAKTU KONTAK ARANG AKTIF UNTUK MENURUNKAN BILANGAN PEROKSIDA PADA MINYAK GORENG BEKAS PAKAI - Tuti Rustiana; Dinar Rahayu (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2021)
Vegetable oil in the cooking process usually is used multiple times to fry food. This process exposes the oil to heat and oxidation. The oil itself is lipid. Lipid is a triglyceride, which means three carboxylic acids are bonded to one molecule of glycerol to form of ester. Exposing triglyceride to heat and oxidation causes it to deteriorate and break into smaller molecules such as aldehyde, ketones, and hydrocarbons. This molecule causes rancidity. Rancidity can be measured in terms of the amount of hydroperoxide presents in oil in mEq of O2/Kg. The peroxides present oxidize the iodide to iodine and the iodine is then titrated to a colorimetric endpoint using sodium thiosulfate with starch as an indicator. The amount of iodine produced is directly proportional to the peroxide value. The research has been conducted to reduce the peroxide value of used cooking oil using adsorption. The adsorbent used here is activated charcoal with a concentration of 3% and particle size of 100 Mesh. Contact time with oil is varied, ranged from 30 to 90 minutes. Statistic treatment of t-student test is performed between peroxide value before and after treatment and it is found that the difference is significant. That means active charcoal can decrease peroxide value. One way of ANOVA test among contact times (30, 60, 90 minutes) proves there is no significant difference, leading to the conclusion that activated charcoal at 3% and particle size 100 Mesh can decrease the peroxide value of oil in only 30 minutes of contact time.